The role of a single gene encoding the Single von Willebrand factor C-domain protein (SVC) in bumblebee immunity extends beyond antiviral defense. (December 2017) - Wang, Haidong; Smagghe, Guy; Meeus, Ivan
Abstract: The Single von Willebrand factor C-domain proteins (SVCs) are a group of short proteins mainly found in arthropods. They are proposed to be responsive in relation to environmental challenges including the nutritional status, bacterial and viral infections. The SVC protein Vago acts as a cross-talk molecule between the small interfering RNA (siRNA) pathway and the Jak/STAT pathway upon viral infection in Drosophila melanogaster and Culex mosquito cells. Unlike flies and mosquitoes that possess diverse SVCs, most bee species only have one of which the function remains unclear. Here we investigated whether this single SVC within the genome of the bumblebee Bombus terrestris is also involved in the host antiviral immunity and whether links with other immune pathways can be found. We can show the presence of two key characteristics of Vago linked with the single SVC in B. terrestris ( BtSVC ). The antiviral character is proven by silencing BtSVC, which lead to increased Israeli acute paralysis virus (IAPV) levels in the fat body. Second, the silencing of BtDicer-2 resulted in a lower expression of BtSVC and increased IAPV levels, confirming the link between Dicer-2 and Bt SVC. We were, however, unable to demonstrate a third known role of Vago in the activation of the Jak/STAT pathway. This is probably because we lack good markers for this pathway in bumblebees. Interestingly, we found that BtSVC contributes to the basal expression levels of four antimicrobial peptide (AMP)-coding genes in the fat body of the bumblebees. Therefore, the single SVC gene in bumblebees may be involved in both host antiviral immunity and basal AMPs expression. Graphical abstract: Highlights: In the bumblebee Bombus terrestris, silencing BtSVC resulted in increased Israeli acute paralysis virus (IAPV) level. Silencing BtDicer-2 resulted in lower BtSVC expression and increased IAPV level. BtSVC is also involved in the basal expression of AMP genes.